The Phenomenon of Mukbang on Social Media: Sayyid Qutbuh’s Perspective on The Tafsir of The Qur’an - Ummiyah, Meity; Zuhri, Ahmad; Aisyah, Nur (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
In Islam, all excesses are prohibited because they will have fatal consequences, such as mukbang which can damage the health of the human body. In this study, the analysis of the Mukbang phenomenon on social media was studied: